PROBLEMATIKA PEMBELAJARAN AKIDAH AKHLAK DI SEKOLAH DASAR - Ali Imron (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract The study, entitled "The Problematics of Moral Learning in Elementary Schools Nurul Islam Purwoyoso Semarang" uses a qualitative research approach, with the aim to find out: the learning process of moral behavior in elementary schools, problems in the learning of moral code in elementary schools and solutions to overcome them. After conducting research the results are: first, the process of learning the moral code at SD Nurul Islam Purwoyoso is carried out by planning learning, carrying out learning using the lecture method, question and answer and ending with closing learning. Secondly, problems in learning moral behavior in Nurul Islam Purwoyoso Elementary School include problems with teachers, problems in classroom management and learning methods and problems in students. Third, the solution to overcome the problem of moral learning in Nurul Islam Purwoyoso Elementary School is by planning learning well and according to the needs of the school, using learning methods that create active learning, implementing learning evaluations well, providing learning media, mastering more material by directing learning active students rather than dictating, and cooperation among principals, teachers and parents. Keywords: Problems, Learning, Morals and Morals